Effect of infection with the ts22 mutant of Semliki Forest virus on development of the central nervous system in the fetal mouse. - Mabruk, M J (J Virol, 1989)
The A7 strain of Semliki Forest virus induces rapid fetal death in pregnant mice, whereas the ts22 mutant derived from it is teratogenic for a proportion of fetuses. Both A7 and ts22 induce viremia and infect the central nervous systems and fetuses of pregnant mice. Using immunogold-silver staining, a cDNA probe for a Semliki Forest virus nonstructural sequence, and a riboprobe derived from the same sequence, we showed that the skin and musculoskeletal systems of fetuses from mothers infected with ts22 were often heavily infected but the central nervous systems were not labeled before day 17 of pregnancy. Damage to the neural tube, including open-neural-tube defects, was detected in fetuses following infection of the mother at days 8 and 10 of pregnancy with both A7 and ts22. For ts22, neural tube damage induced by fetal infection before day 17 of pregnancy appeared to be indirect and caused by virus infection of mesenchymal cells surrounding the developing neural tube. IMAGES: